Associations of Changes in Cardiorespiratory Fitness and Symptoms of Anxiety and Depression With Brain Volumes: The HUNT Study - Zotcheva, Ekaterina; Pintzka, Carl W. S.; Salvesen, Øyvind; Selbæk, Geir; Håberg, Asta K.; Ernstsen, Linda (Frontiers in Behavioral Neuroscience, 2019)
Objective: We investigated the independent and joint associations of changes in estimated cardiorespiratory fitness (eCRF) and symptoms of anxiety and depression with brain volumes in individuals from the general population. Method: 751 participants (52% women, aged 50–67 years) from the Nord-Trøndelag Health Study (HUNT) MRI cohort were included. eCRF obtained from a non-exercise algorithm and symptoms of anxiety and depression were assessed twice; at HUNT2 (1995–97) and HUNT3 (2006–08). Brain MRI was performed shortly after HUNT3. Brain parenchymal fraction (BPF), bilateral hippocampal and total cortical volume were extracted from brain MRI obtained at 1.5T, using FreeSurfer and Statistical Parametric Mapping. Results: Multiple regression revealed that participants whose eCRF increased had larger BPF (β = 0.09, 95% CI 0.02, 0.16) and larger hippocampal volume (β = 0.09, 95% CI 0.03, 0.16) compared to participants whose eCRF remained low. Participants whose eCRF remained high had larger BPF (β = 0.15, 95% CI 0.07, 0.22) and larger cortical volume (β = 0.05, 95% CI 0.01, 0.09). Participants whose anxiety symptoms worsened had smaller BPF (β = −0.09, 95% CI −0.15, −0.02) and cortical volume (β = −0.05, −0.08, −0.01) than participants whose anxiety symptoms remained low. Each ml/kg/min increase in eCRF was associated with larger cortical volume among individuals with worsening of anxiety symptoms (β = 0.13, 95% CI 0.001, 0.27), and larger BPF among individuals whose depressive symptoms improved (β = 0.28, 95% CI 0.02, 0.53). Conclusion: Promoting exercise intended to improve eCRF may be an important public health initiative aimed at maintaining brain health among middle-aged individuals with and without changing psychological symptoms.